Governance and Management of Zakat and Waqf: Evidence-Based Practices from Southeast Asia and the Middle East – A Systematic Literature Review - Eny Latifah; Farhan Ahmad (MADINAH, 2026)
This study aims to analyze evidence-based practices in the governance and management of zakat and waqf in Southeast Asia and the Middle East. The research adopts a qualitative approach using a literature review and comparative analysis of selected countries with relatively advanced zakat and waqf management systems. The findings reveal that the effectiveness of zakat and waqf governance is strongly influenced by robust regulatory frameworks, institutional professionalism, transparency and accountability in fund management, and the adoption of digital technologies. Southeast Asian countries tend to excel in digital innovation and system integration, while Middle Eastern countries demonstrate strengths in regulatory support and the large-scale management of waqf assets. The study also identifies key challenges, including the lack of global standardization, limited inter-institutional coordination, and varying levels of public literacy regarding zakat and waqf. Therefore, an adaptive, transparent, and collaborative governance model is essential to enhance the effectiveness of zakat and waqf management in supporting socio-economic development within the Muslim community.